Integrasi Arisan Telur dan Ternak Ayam Petelur untuk Pencegahan Stunting Balita - Dianti Ias Oktaviasari; Mia Ashari Kurniasari; Reny Nugraheni; Ratna Frenty Nurkhalim (GUYUB: Journal of Community Engagement, 2025)
Stunting remains a chronic nutritional problem among under-five children, closely associated with inadequate intake of animal-based protein and limited access to nutritious food at the household level. In Bareng Village, Sawahan District, Nganjuk Regency, data from Posyandu Mambang in 2025 revealed 12 stunted children, 37 undernourished children, and 22 children with no weight gain, accompanied by low egg consumption. This community service program aimed to improve the availability and intake of animal protein among under-five children by utilizing local potential through small-scale household laying-hen farming integrated with an egg-sharing (arisan telur) mechanism at Posyandu Mambang. The program was implemented from March to November 2025 using an Asset-Based Community Development (ABCD) approach, including training on laying-hen management, distribution of laying hens to target families, and optimization of the egg-sharing system. Evaluation results showed that the average weekly egg consumption among children increased from 1.1 eggs at baseline to 2.4 eggs in October 2025 and reached 3.2 eggs by November 2025. The proportion of children consuming at least three eggs per week increased from 16% to 68%. In addition, the program enhanced the knowledge and skills of families and community health volunteers in poultry management and nutrition education. In conclusion, integrating an egg-sharing system with household laying-hen farming based on local resources is effective in gradually and sustainably increasing animal protein intake among under-five children and has the potential to support stunting prevention efforts in rural areas.